KESESUAIAN LAHAN REKLAMASI UNTUK REVEGETASI TANAMAN MAHONI (SWIETANIA MACROPHYLLA) DAN TANAMAN SUNGKAI (PARONEMA CANESCENS) PADA PT. BHUMI RANTAU ENERGI DI KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Yusveni Farizarakhmi; Emmy Sri Mahreda; Basir Achmad; Kissinger Kissinger (Universitas Lambung Mangkurat, 2023)
The mining sector is one of the main economic sectors in Indonesia, including coal. Given the importance of ecosystem sustainability, reclamation and revegetation activities are very important. The aims of this study were (1) to analyze the characteristics of soil fertility at the reclamation and revegetation sites of PT. Bhumi Rantau Energi and (2) analyze land suitability of PT. Bhumi Rantau Energi which has been planted with mahogany (Swietenia macrophylla) and sungkai (Peronema canescens) plants.. The approach used in this study is a quantitative method and descriptive analysis, with a research implementation time of 3 (three) months. The research was conducted at Rinjani and Merapi which is a reclamation and revegetation area of PT. Bhumi Overseas Energy. The objects in this study were soil samples in Rinjani D3 planting year 2017 with an area of 2.39 ha and measurements of Mahogany, Sungkai and Sengon vegetation on Rinjani D3 planting year 2017 with an area of 2.39 ha, Rinjani E2 planting year 2018 with an area of 6, 40 ha and Merapi F9 planting year 2019 with an area of 18.62 ha. The results showed that the fertility of the soil was in the low fertility class. However, the success of growing the main types of sengon and inlay types of mahogany and sungkai in post-coal mining revegetation land was in the high category. Sungkai inserts have better diameter and plant height than mahogany inserts. For land suitability results, the mahogany insert is thought to be relatively slightly better than the sungkai plant. Parameter differences that occur in the annual average rainfall. The results of the land suitability analysis obtained direct engineering improvements to be carried out by improving the parameters of soil pH, soil fertility and soil depth.